Impact of Gang Migration: Effective Responses by Law Enforcement Agencies in the United States, 1992 - Maxson, Cheryl L. ([Verlag nicht ermittelbar], 1999)
This study was the first attempt to investigate gang migration systematically and on a national level. The primary objectives of the study were (1) to identify the scope of gang migration nationally, (2) to describe the nature of gang migration, (3) to assess the impact of gang migration on destination cities, and (4) to describe the current law enforcement responses to the migration of gangs and identify those that appeared to be most effective for various types of migration. Two phases of data collection were used. The major objective of the initial phase was to identify cities that had experienced gang migration (Part 1). This was accomplished by distributing a brief mail questionnaire in 1992 to law enforcement agencies in cities identified as potential gang or gang migration sites. The second major phase of data collection involved in-depth telephone interviews with law enforcement officers in cities that had experienced gang migration in order to develop descriptions of the nature of migration and police responses to it (Part 2). For Part 1, information was collected on the year migration started, number of migrants in the past year, factors that deter gang migration, number of gang members, names of gangs, ethnic distribution of gang members and their drug market involvement, number of gang homicides, number of 1991 gang "drive-bys", and if gangs or narcotics were specified in the respondent's assignment. For Part 2, information was collected on the demographics of gang members, the ethnic percentage of drug gang members and their involvement in distributing specific drugs, and the influence of gang migrants on local gang and crime situations in terms of types and methods of crime, drug distribution activities, technology/equipment used, and targets of crime. Information on patterns of gang migration, including motivations to migrate, drug gang migration, and volume of migration, was also collected. Local responses to gang migration covered information sources, department policies relative to migration, gang specialization in department, approaches taken by the department, and information exchanges and coordination among local, state, and federal agencies.